On the interaction of triarylmethane dye crystal violet with LAPONITE® clay: using mineral nanoparticles to control the dye photophysics. Issue 26 (14th July 2015) - Ley, C.; Brendlé, J.; Walter, A.; Jacques, P.; Ibrahim, A.; Allonas, X.
<x xml:space="preserve">Abstract</x> The combination of an organic dye with clays leads to very interesting hybrid materials with original properties.